PREVALÊNCIA DA COINFECÇÃO DE HIV/SÍFILIS EM PACIENTES EM ACOMPANHAMENTO NO CENTRO DE APOIO ESPECIALIZADO (CAE) DE ARAGUARI-MG. - Costa Monteiro, Victor; Dantas, Daniel; Moraes, Gustavo; de Moura Torres, Káliston; Miranda Chaves Teles, Renatha; Resende Freitas, Ricardo; Lima Nakao, Rodrigo; Caixeta Andrade, Sabrina; Cláudia Cândida Rodrigues, Maria; Gomes Peixoto, Leonardo (Revista Master - Ensino, Pesquisa e Extensão, 2020)
Sexually Transmitted Infections (STDs) have increased in recent years worldwide. Syphilis and HIV are STDs that pose health challenges, mainly due to the possibility of causing infertility gestational and immune system losses. The aim of this study was to evaluate the prevalence of HIV associated with syphilis coinfection in Araguari-MG and to compare the profiles of patients diagnosed with HIV with those diagnosed with HIV and coinfected with syphilis. A study of the records of the Specialized Support Center in Araguari with 337 patients under treatment from 1998 to October 2019 was performed. Descriptive statistics categorized the samples by sex, age, sexual orientation, color, educational level and length of treatment, thus making it possible to calculate associated prevalence. Chi-square and Student’s t-test compared the frequencies of sociodemographic and clinical variables (p <0.05). The results showed that most of the coinfected are male (88.2%); homosexual (61.2%); with an average age of 34.6 years (+ 9.6) and education level > 12 years (64.7%); white (70.6%) and do not use injecting drugs (91.2%). In addition, the prevalence rate of syphilis coinfection in HIV-positive patients is 10.1%. Thus, it is concluded that coinfected patients are mostly male, homosexual, with a medium level of education.